Evaluation of hearing acuity in patients with chronic renal failure by pure tone audiometry - Pathak, Netra A.; Nemade, Sanjana V.; Shinde, Kiran J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Hearing loss is common in patients with chronic renal failure. It is well known that chronic renal failure (CRF) causes different systemic and otorhinolaryngologic manifestations due to the accumulation of nitrogenous waste products. The aim of the study was to evaluate hearing threshold and the severity of hearing loss at different frequencies in patients of chronic renal failure (CRF), and to analyse the role of duration of disease on hearing threshold in patients of CRF. Methods: Fifty two patients of CRF were included in the study. Pure tone audiometry was done in all cases. Results: Majority of the patients were in 21 to 40 year age group (mean: out of 52 patients, 38 patients (73.07%) had sensorineural hearing loss and 14 patients (26.93%) had normal hearing. Majority of the patients with hearing loss had mild (44.73%) or moderate (42.11%) sensorineural hearing loss. On comparison of the mean hearing threshold Group II (duration of disease more than five years- 17 patients) showed a statistically significant difference (P<0.05) in mean hearing threshold at 250 Hz. Conclusions: Hearing loss is present in majority of the patients of CRF. Most of the cases have mild to moderate sensorineural hearing loss. High frequency hearing loss in chronic renal failure is related to the duration of the disease, duration of haemodialysis’ and internal homeostasis, namely hyponatremia.